2000
DOI: 10.1099/00207713-50-6-1989
|View full text |Cite
|
Sign up to set email alerts
|

Methanomicrococcus blatticola gen. nov., sp. nov., a methanol- and methylamine-reducing methanogen from the hindgut of the cockroach Periplaneta americana.

Abstract: A small irregular coccoid methanogenic bacterium (PA T ) was isolated from the hindgut of the cockroach Periplaneta americana. Fluorescence microscopy and transmission electron microscopy of the hindgut of P. americana suggest that the organism occurs abundantly in the microbiota attached to the hindgut wall. The strain produces methane by the reduction of methanol and methylated amines with molecular hydrogen. Acetate, coenzyme M, yeast extract, tryptic soy broth and vitamins are required for growth. The cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 28 publications
5
71
1
Order By: Relevance
“…but are generally not a major group (Janssen and Kirs, 2008). Members of this genus also appear to convert hydrogen plus methyl compounds to methane (Sprenger et al, 2000).…”
Section: Overview Of Rumen Ecology/methanogensmentioning
confidence: 99%
See 1 more Smart Citation
“…but are generally not a major group (Janssen and Kirs, 2008). Members of this genus also appear to convert hydrogen plus methyl compounds to methane (Sprenger et al, 2000).…”
Section: Overview Of Rumen Ecology/methanogensmentioning
confidence: 99%
“…but are generally not a major group (Janssen and Kirs, 2008). Members of this genus also appear to convert hydrogen plus methyl compounds to methane (Sprenger et al, 2000).The little that is known about members of Methanoplasmatales indicates that they too are methylotrophic methanogens, also metabolising hydrogen plus methyl compounds to methane in the same stoichiometry as Methanosphaera (Paul et al, 2012; J. Jeyanathan, R. Ronimus and P. H. Janssen, unpublished data). Their abundance is also likely to be limited by methyl compound availability.…”
mentioning
confidence: 99%
“…Ethane (1 ml) was added as an internal standard (11). At regular intervals, gas samples (200 l) were taken using hypodermic needles and 1-ml syringes and analyzed for methane and hydrogen by gas chromatography (21,22). As a rule, gases were measured at 3 h and 17 to 22 h after the start of the incubation.…”
Section: Methodsmentioning
confidence: 99%
“…Gut segments were incubated in 2 ml of HEPES buffer (50 mM HEPES, 50 mM NaCl, 5 mM Na 2 HPO 4 , 1.5 mM KH 2 PO 4 [pH 7.0]) in 10-ml vials (21). Since pilot experiments had shown that under these conditions hydrogen production was linear for up to 29 h and the production of methane from endogenous substrates was linear for up to 48 h, gas production rates were analyzed using the same protocol as for living cockroaches.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation